Crises, inquiries and the politics of blame / Sandra L. Resodihardjo. - Resodihardjo, Sandra L. (Palgrave Macmillan, 2020)
Crises are followed by questions and the accountability phase inevitably involves the blame game. In using in-depth case study analysis of tragic incidents at festivals, Sandra Resodihardjo explores why and how blame games start, evolve and are then influenced by a variety of factors. This is a fascinating read, when things go badly wrong the cycle of blame is often complex, involving multiple actors and organisations often battling to frame the event to their own agenda. This should be essential reading not just for scholars studying this critical area of public policy, but practitioners who would undoubtedly learn a lot from the analytical oversight and forensic detail contained in this excellent book.